Simulation analysis of the effects of undulation amplitude change on the performance during the underwater dolphin kicking - Sugimoto, S.; Nakashima, M.; Nomura, T. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The objectives of this study were to conduct the musculoskeletal simulation for the breast, back, and butterfly strokes using a musculoskeletal simulator which was recently developed by the authors, and to examine the validity of the simulator. Based on educational movies of an elite swimmer, standard swimming motions for the three strokes were constructed and input to the simulator. The body geometry of averaged Japanese male of 20-30 years old was also input. Many reasonable tendencies were obtained in the simulation results. These results suggested that the musculoskeletal simulation for swimming will be a powerful tool to assess the swimming motion.